2016
DOI: 10.1007/s00259-016-3491-5
|View full text |Cite
|
Sign up to set email alerts
|

SPECT myocardial blood flow quantitation toward clinical use: a comparative study with 13N-Ammonia PET myocardial blood flow quantitation

Abstract: Quantitation with SPECT technologies can be accurate to measure myocardial blood flow as PET quantitation while comprehensive imaging factors of SPECT to derive the variability between these two approaches were fully addressed and corrected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 28 publications
0
26
1
1
Order By: Relevance
“…The feasibility of this approach has been demonstrated in a large animal model, 155 but at this time SPECT MBF and MFR measurements in humans are very new. While the results have been very encouraging, investigations with both conventional rotating systems 156,157 and non-rotating cardiac cameras 15,17,158,159 have been limited to single-center feasibility studies. While the benefits of PET-based MBF/MFR are clear, [160][161][162][163] no published study has currently evaluated the incremental diagnostic and prognostic value of SPECT MBF and MFR measurements; more investigations are ongoing in this area.…”
Section: Spect Myocardial Blood Flow Quantitation Introductionmentioning
confidence: 99%
“…The feasibility of this approach has been demonstrated in a large animal model, 155 but at this time SPECT MBF and MFR measurements in humans are very new. While the results have been very encouraging, investigations with both conventional rotating systems 156,157 and non-rotating cardiac cameras 15,17,158,159 have been limited to single-center feasibility studies. While the benefits of PET-based MBF/MFR are clear, [160][161][162][163] no published study has currently evaluated the incremental diagnostic and prognostic value of SPECT MBF and MFR measurements; more investigations are ongoing in this area.…”
Section: Spect Myocardial Blood Flow Quantitation Introductionmentioning
confidence: 99%
“…CFR is now available noninvasively on multimodalities such as dynamic CT or MRI perfusion scan (15,16), SPECT (17), and flow velocity on MRI (18). The cold pressor test (CPT) is another method for stress testing in addition to adenosine stress.…”
Section: Future Directions and Alternativesmentioning
confidence: 99%
“…The authors also demonstrated that quantitative flow results are potentially less accurate if these physical corrections are not performed. In another recent study from the same group, 28 patients were studied with conventional SPECT/ CT, and the flow-dependent extraction fraction relationship was determined by the fitting of the SPECT quantification results to the 13N-ammonia results [75]. With this approach, very good correlations were obtained for global and regional MBF and MFR by technetium (99mTc) sestamibi SPECT and 13N-ammonia PET (R2=0.71–0.92).…”
Section: Dynamic Flow With Spectmentioning
confidence: 99%
“…The ROC curves comparing the ML algorithm versus expert visual analysis for the detection of obstructive coronary artery disease. With kind permission of Springer: Journal of Nuclear Cardiology, Improved accuracy of myocardial perfusion SPECT for detection of coronary artery disease by machine learning in a large population, Volume 20, 2013, pp 553–562, Arsanjani et al [75]. …”
Section: Figurementioning
confidence: 99%